Safety and Tolerability of BRAF Inhibitor and BRAF Inhibitor-Based Combination Therapy in Chinese Patients With Advanced Melanoma: A Real World Study - Liu, Xing; Li, Jing-jing; Ding, Ya; Li, Dan-dan; Wen, Xi-zhi; Weng, De-sheng; Wang, Jiu-hong; Jiang, Hang; Zhang, Xiao-shi (Frontiers in Oncology, 2021)
A previous study has suggested the toxicity spectrum between Chinese and Caucasian melanoma patients treated with BRAFi may be different. The purpose of the present study was to assess the safety and tolerability of BRAFi and BRAFi-based combination therapies (MEK inhibitors [MEKi] or anti-programmed death-1 [PD-1] antibody) in Chinese patients with BRAF V600E/K mutation-positive metastatic melanoma. We also investigated whether treatment-related adverse events (AEs) were correlated with prognosis. This retrospective study collected data from 43 melanoma patients with BRAF V600E/K mutation-positive metastatic melanoma from a single Chinese cancer center. Twelve patients received BRAFi monotherapy, 12 patients received BRAFi+MEKi, and 19 patients received BRAFi combined with anti-PD-1 antibody. The median follow-up time was 19 months. In the BRAFi group, the most common AEs were rash, palmoplantar erythrodysesthesia, and arthralgia. Four of 12 (30.0%) patients experienced grade 3/4 treatment-related AEs. All grade AEs in the BRAFi+MEKi group were similar to the BRAFi group, except for higher pyrexia (58.3%) and lower incidence of cutaneous AEs. Three of 12 (25%) patients experienced grade 3/4 AEs, especially pyrexia (16.7%). In the BRAFi+anti-PD-1 antibody group, any grade AEs were similar to those of the BRAFi group, except for increased aminotransferase level (36.8%), increased bilirubin (31.6%), and hypothyroidism (15.8%). Eleven of 19 (57.9%) patients experienced grade 3/4 AEs and 4 of 19 (21%) patients discontinued therapy due to AEs. Treatment-related hepatotoxicity (trHE), defined as treatment-related increase in ALT and/or AST levels and/or blood bilirubin levels, was only AE analyzed as a significant poor-prognosis indicator in this study. The median progression-free survival of patients with trHE (41.9%) was 8.0 months compared with 18.0 months of those without trHE (p=0.046, hazard ratio (HR)=2.116). Moreover, this association was independent of medication regimens (p=0.014, HR =2.971). The ORR of patients with trHE was significantly lower than in those without trHE (44.4% vs. 60.0%, p=0.024), and we observed a similar trend in patients treated with BRAFi, BRAFi+MEKi and BRAFi+anti-PD-1 antibody. In conclusion, BRAFi and BRAFi-based combination therapy were tolerable with reversible AEs in Chinese melanoma patients. The trHE in patients receiving BRAFi and BRAFi-based regimens might indicate poor-therapy related prognosis.